Diversity of dung beetles (Coleoptera: Scarabaeidae) in three urban areas from Colombian Caribbean - Sermeño-Correa, Carlos (2022)
In this paper, diversity and composition of dung beetles assemblage was study in three urbanized areas with different ecological characteristics from Sucre department , Colombia. Individuals were captured with baited pitfall traps. Sampling effort, range-abundance curves, alpha and beta diversity indices were estimated and compared among the sites. Seven hundred ten individuals grouped into nine genera and 13 species were recorded. The completeness analysis yielded values above 97%. The most diverse assemblage in any of the three orders of "q" was found in the site with a mixture of buildings, gardens, and a patch of secondary vegetation forest, followed by the site with few facilities and open green spaces, and the least diverse site corresponded to the area surrounded by buildings with little vegetation cover. Sorensen-Dice index similarity among the three sites was 38%. The range-abundance curves showed higher species equitability in the most diverse site. The results show that the beetle assemblage composition depends on environmental conditions and the degree of urbanization. It was also evident that some species have high adaptability to urban spaces and others are potentially at risk of local extinction events.